Scrapbook 02 - http://id.worldcat.org/fast/1479363 (1972)
Consists of clippings; including illustrations; from newspapers and journals relating to gender identity. Clippings may or may not contain source information. Identifiable sources include Daily Mirror; the Lancet; Evening Mail; Birmingham Gay Liberation; and Gay Liberation Front. The scrapbook is hand-numbered 2 on upper right corner of cover.